Anion inhibition profiles of the complete domain of the η-carbonic anhydrase from Plasmodium falciparum. Issue 18 (15th September 2016) - Del Prete, Sonia; Vullo, Daniela; De Luca, Viviana; Carginale, Vincenzo; di Fonzo, Pietro; Osman, Sameh M.; AlOthman, Zeid; Supuran, Claudiu T.; Capasso, Clemente
Graphical abstract: Abstract: We have cloned, purified and investigated the catalytic activity and anion inhibition profiles of a full catalytic domain (358 amino acid residues) carbonic anhydrase (CA, EC 4.2.1.1) from Plasmodium falciparum, PfCAdom, an enzyme belonging to the η-CA class and identified in the genome of the malaria-producing protozoa. A truncated such enzyme, PfCA1, containing 235 residues was investigated earlier for its catalytic and inhibition profiles. The two enzymes were efficient catalysts for CO2 hydration: PfCAdom showed a k cat of 3.8 × 10 5  s −1 and k cat / K m of 7.2 × 10 7  M −1  × s −1, whereas PfCA showed a lower activity compared to PfCAdom, with a k cat of 1.4 × 10 5  s −1 and k cat / K m of 5.4 × 10 6  M −1  × s −1 . PfCAdom was generally less inhibited by most anions and small molecules compared to PfCA1. The best PfCAdom inhibitors were sulfamide, sulfamic acid, phenylboronic acid and phenylarsonic acid, which showed K I s in the range of 9–68 μM, followed by bicarbonate, hydrogensulfide, stannate and N, N -diethyldithiocarbamate, which were submillimolar inhibitors, with K I s in the range of 0.53–0.97 mM. Malaria parasites CA inhibition was proposed as a new strategy to develop antimalarial drugs, with a novel mechanism of action.